The effects of Corporate Social Responsibility (CSR) on Chinese consumers' buying behaviour in Dairy Industry - SU, YI-Jie (2016)
There have been substantial researches investigating the effects of corporate social responsibility (CSR) on corporate financial performance and long-term economic well-being. However, relatively little of researches or studies have been conducted based on the correlation of CSR and consumer behaviours, especially in developing countries or emerging markets. In this regard, this study addresses certain issues examining the effects of CSR on Chinese consumers’ buying behaviours in the industry of dairy by using a quantitative research method. Based on prior academic literatures in this field and attitude-behaviour theoretical framework, this paper postulates that CSR influence consumers’ attitudes, evaluation and identification towards a CSR brand. At the same time, customer’s attitudes of CSR brands, as their affective states of mind, will also influence their subsequent purchase behaviours (e.g., purchase intentions, loyalty intentions, word-of-mouth) regarding firms with CSR practices. 161 valid questionnaires were collected online and data in this case was analysed by using SPSS. Results of this research find that CSR has a significant effect on increasing customers’ emotions and evaluations towards CSR brands. But the effects of it on consumers’ behavioural intentions are more complicated than expectation. In addition, the study provides empirical evidence to support the link between customers’ knowledge of CSR and their buying behaviours towards CSR dairy corporations in the context of China. This paper was finally concluded by discussing the implications of these findings for managers and further research.